Su alcune “eresie” di Federigo Enriques: l’idea di sistema come un processo di auto-delimitazioni successive - Castellana, Mario (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2023)
Today the idea of complexity has imposed itself in several fields of research with all its vast articulated conceptual equipment through various “ways”, as Edgar Morin would put it. Therefore, it could be useful to take into consideration the way it was declined by Federigo Enriques (1871-1946). This peculiar aspect emerged in the constant historicalepistemological reflections that accompanied his entire scientific activity from the Problems of Science (1906) to his last works of the 1930s. In these texts, it is possible to detect some of the crucial aspects of the subsequent philosophical-scientific debate, which will make the writer Paul Valéry admit to agreeing with what he calls his ‘heresies’. One of these lesser known “heresies” is that which concerns the question of the processes of conceptual selfdelimitation within any theoretical system. Enriques approaches the question with a style of thinking close to the spirit, in the Bachelardian sense, of the epistemology of complexity, only to find a more organic relief in the fundamental contributions of Jean Piaget, following in his wake.